استثمار صناديق التأمين التعاوني الإسلامي : التكافل المتعلق بالاستثمارات نموذجا - Hasnan Abu Bakar (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
This study examines investment from the view of Islamic jurisprudence and finance as well as Islamic insurance as a system and a contract. Furthermore, it identifies the application of investment in Islamic insurance through Investment-Linked Takaful products by one Takaful operator in Malaysia, namely Prudential BSN Takaful, in order to recommend Islamic solutions to some essential issues implemented by the company. Those issues are the amalgamation of contracts, cleansing of returns and zakat of the takaful investment funds. The researcher adopted inductive, analytical and field research methods in this study. Some key findings include the amalgamation of contracts in Investment-Linked Takaful products as applied by the company is in accordance with Islamic law, the necessity of cleansing at least 5% of the investment funds from net profits and the necessity of zakah 'urud al-tijarah (zakah on business inventory) on participants whereas the Takaful operator has to pay either zakah on earned income or zakah of corporation.